Basic Life Support Access to Injectable Epinephrine across the United States. (4th July 2017) - Brasted, Ian D.; Dailey, Michael W.
Abstract: Background: Aggressive epinephrine administration has growing support in the treatment of anaphylaxis, a life-threatening allergic reaction. Emergency Medical Services (EMS) providers are frequently in a position to provide the first care to someone experiencing an anaphylactic reaction. Intramuscular injection of epinephrine is the definitive pharmacologic treatment for many associated symptoms. While easy to use, epinephrine autoinjectors (EAI) are prohibitively expensive, having increased in price ten-fold in ten years. Some states and EMS departments have begun expanding the scope of practice to allow Basic Life Support (BLS) providers, previously restricted to noninvasive therapies, to administer epinephrine by syringe.Objectives: To compile a current and comprehensive list of how epinephrine is carried and used by EMS across the USA.Methods: An online survey focusing on anaphylaxis protocols and epinephrine administration was sent to state EMS medical directors and officials in all 50 states. Follow-up telephone calls were made to ensure compliance. Data were analyzed with descriptive statistics.Results: Forty-nine of the 50 states in the USA provided a survey response. Texas responded but declined to participate in the survey because of practice variability across the state. In the other states, the form of epinephrine allowed or required on BLS ambulances was consistent with the scope of practice of their Basic Emergency Medical Technician (EMT). Thirteen states had training programs to allow BLS providers to inject epinephrine; 7 were considering it; 29 were not. Twenty-seven states specified EAI as the only form of epinephrine required or allowed on their BLS ambulances. No states reported allowing any level of EMS provider below EMT to use alternatives to EAI.Conclusion: This study confirms that many states have expanded the training of BLS providers to include the use of syringe injectable epinephrine. Even so, the majority of states relied on EAI in BLS ambulances.